New cyslabdans B and C, potentiators of imipenem activity against methicillin-resistant Staphylococcus aureus produced by Streptomyces sp. K04-0144 - Nobuhiro Koyama; Yuriko Tokura; Yoko Takahashi; Hiroshi Tomoda (Elsevier, 2011)
From a further purification study, two new congeners designated cyslabdans B (1) and C (2) were isolated along with previously reported cyslabdan (cyslabdan A (3) in this study) from the culture broth of Streptomyces sp. K04-0144. The structure was elucidated by various spectroscopy including NMR, revealing that 1 and 2 was 18-hydroxy and 1'-methoxy cyslabdan, respectively. Compounds 1 and 2 were found to potentiate imipenem activity against methicillin-resistant Staphylococcus aureus by 123 fold and 533 fold, respectively. Comparison with the activity of compound 3 indicated that the introduction of a hydrophilic group at the dimethyl moiety of the decalin ring was unfavorable for its activity.